2011
DOI: 10.1002/eji.201141845
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐γ elevates airway hyper‐responsiveness via up‐regulation of neurokinin A/neurokinin‐2 receptor signaling in a severe asthma model

Abstract: The adoptive transfer of OVA-specific Th1 cells into WT mice followed by OVA inhalation induces a significant elevation of airway hyper-responsiveness (AHR) with neutrophilia but not mucus hypersecretion. Here, we demonstrate that the airway inflammation model, pathogenically characterized as severe asthma, was partly mimicked by i.n. administration of IFN-c. The administration of IFN-c instead of Th1 cells caused AHR elevation but not neutrophilia, and remarkably induced neurokinin-2 receptor (NK2R) expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Then, we found that the Th2-mediated asthma model was steroid sensitive, but the Th1 and Th17 models were steroid resistant, suggesting that both Th1 and Th17 cause steroid-resistant severe airway inflammation. Furthermore, we performed intranasal injection with IFN-g and confirmed the direct effect of IFN-g on the increased AHR (11). Then, we demonstrated that the expression level of neurokinin-2 receptor (NK2R) was remarkably enhanced in the Th1-dependent asthma models and in the lung after IFN-g injection.…”
mentioning
confidence: 63%
“…Then, we found that the Th2-mediated asthma model was steroid sensitive, but the Th1 and Th17 models were steroid resistant, suggesting that both Th1 and Th17 cause steroid-resistant severe airway inflammation. Furthermore, we performed intranasal injection with IFN-g and confirmed the direct effect of IFN-g on the increased AHR (11). Then, we demonstrated that the expression level of neurokinin-2 receptor (NK2R) was remarkably enhanced in the Th1-dependent asthma models and in the lung after IFN-g injection.…”
mentioning
confidence: 63%
“…IFN-␥ from Th1 cells is required for the induction of severe airway hyperresponsiveness (30). Furthermore, we demonstrated that resveratrol inhibits TLR3 signaling, M2R expression, and IFN-␥ production.…”
mentioning
confidence: 64%
“…The activation of cytokines, chemokines, and IFNs in the host after binding viral PAMPs leads to an antiviral state and activates the adaptive immune response. Upon RSV infection, the signal initiated from TLR3 and TLR4 activates the adaptor protein TRIF (7,27,30). Specifically, the RSV fusion protein can bind to TLR4, which induces the production of interleukin-1␤ (IL-1␤), IL-6, IL-8, and tumor necrosis factor alpha (TNF-␣) (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that neuropeptide signaling through NK2R was correlated with airway hyperresponsiveness in mouse severe asthma models. 3 Moreover, we found that the NKA-NK2R signaling pathway was involved in the antigen-presenting function of murine dendritic cells (DCs) and that NK2R expression on DCs was enhanced by Ohtake 8 IFN- and LPS stimulation in a STAT-1-dependent manner. 4 Additionally, we confirmed that human DCs significantly upregulated gene expression levels of NK2R and TAC-1, which encoded Substance P and Neurokinin A, after IFN- or poly I:C stimulation, suggesting possible roles of neuropeptide signaling in human DCs.…”
Section: Ohtakementioning
confidence: 99%